2012
DOI: 10.4049/jimmunol.1200956
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor γ B Cell-Specific–Deficient Mice Have an Impaired Antibody Response

Abstract: Peroxisome proliferator-activated receptors (PPARs) are members of the nuclear hormone receptor superfamily. PPARγ, a ligand activated transcription factor, has important anti-inflammatory and anti-proliferative functions and it has been associated with diseases including diabetes, scarring and atherosclerosis among others. PPARγ is expressed in most bone marrow derived cells and influences their function. PPARγ ligands can stimulate human B cell differentiation and promote antibody production. A knowledge gap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
(57 reference statements)
0
30
0
Order By: Relevance
“…C57BL/6J male mice, 8–10 weeks old (The Jackson Laboratory, Bar Harbor, ME), were immunized by intraperitoneal (i.p.) injection (22). Mice were immediately given a second injection in the same site (i.p.)…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…C57BL/6J male mice, 8–10 weeks old (The Jackson Laboratory, Bar Harbor, ME), were immunized by intraperitoneal (i.p.) injection (22). Mice were immediately given a second injection in the same site (i.p.)…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence minus one (FMO) controls were included in each staining protocol and used to set specific gates (22, 26, 27). 6-peak validation beads were used for calibration during the time course analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, some studies reported the beneficial effects of exogenous treatment of PPARγ ligands in preclinical mouse models of asthma, with reduced serum levels of Th2 cytokines that regulate B cell IgE production (48,49). However, our lab has previously shown direct effects of PPARγ ligands on human B cells by enhancing differentiation and promoting IgG antibody production (17). Here, we show that 17-HDHA in combination with dexamethasone promoted autologous PPARγ ligand production, which is associated with increased IgE production.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we next investigated whether SPMs plus dexamethasone could affect B cell differentiation. One of the important signaling pathways involved in B cell differentiation is the activation of PPARγ by PPARγ ligands (17,18). We measured PPARγ binding activity activated by PPARγ ligands produced by B cells using a PPAR response element-luciferase (PPRE-luciferase) reporter assay.…”
Section: -Hdha and Rvd1 Reduce B Cell Ige Production From Asthma Pamentioning
confidence: 99%